PENDIDIKAN KARAKTER BAGI ANAK USIA DINI DALAM KELUARGA DI DESA TANJUNG KUKUH - Eka Setiawati; Henny Helmi; Azizah Husin; Erna Retna Safitri (STKIP Subang, 2026)
This study aims to describe character education for early childhood within families in Tanjung Kukuh Village. The research uses a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The research informants consisted of the Village Head, the Traditional Leader, and five parents with children aged 5–6 years. The results of the study show that character education within families has been implemented through instilling religious values, honesty, independence, social care, and responsibility in the daily lives of children. The methods used by parents include role modeling, habituation, storytelling, advice, as well as rewards and punishments, with role modeling and habituation being the most dominant methods. Nevertheless, its implementation still faces obstacles, such as parental busyness, lack of consistency, use of gadgets, and environmental influences. Therefore, the role of parents needs to be continuously strengthened so that children's character education can develop optimally.